Analysis of Sombe River Flood Discharge, Porame Village, Sigi Regency - Sulfiati Sulfiati; Suratnan Tahir; Triyanti Anasiru (International Journal of Health, Economics, and Social Sciences (IJHESS), 2020)
This research was conducted in the village of Porame, Sigi Regency, which was conducted from March to August 2017. The Sombe river basin is one of the rivers in the Porame Village, Kab. Sigi, Central Sulawesi Province, which empties into the Palu River, has a length of 10.54 Km and a watershed area of 53.95 KmÂ². High rainfall intensity and uncontrolled land-use changes in the Sombe Watershed Area cause flooding problems, which can ultimately cause a lot of damage. For planning flood control, river safety, and various water structures in the river it is necessary to conduct a hydrological analysis to obtain the magnitude of the flood plain. In this study frequency analysis and Empirical methods are used, namely the Rational, Hasper and Melchior Methods, counting from 10 to 200 years. The calculation of the Sombe River flood discharge used rainfall data at the Porame station, with the recording period from 2005 to 2016 and using a 1: 50,000 scale topographic map. The results of the design flood discharge analysis for each method with various repeat periods obtained the Rational Method that gets the largest value of Flood Discharge that is 663,548 m3 / s; then, the Frequency Analysis Method gets the smallest value 133,057 mm.